PELAJAR-PELAJAR MALAYSIA DI INSTITUSI-INSTITUSI PENGAJIAN ISLAM DI INDIA: ANALISIS BERMULA DARI TAHUN 1947 SEHINGGA 1990 - Abdul Hamid, Faisal@Ahmad Faisal (Journal of Al-Tamaddun, 2009)
This article discusses Islamic High Learning Institution in India that had been a learning centre for Malaysian students since 1947. Beside al-Haramayn in Makkah and Madinah, al-Azhar in Cairo, India also considered as one of the centre for Malaysian student to pursue their studies in Islamic knowledge. The two renowned Islamic institutions in India are Darul ?Ulum Deoband and Darul ?Ulum Nadwat al-?Ulama. This analysis is based on the document of Malaysian student registration in India that had been preserved by National Archives of Malaysia. It contains information of Malaysian?s student that had been registered as a member of Malaysian Student Association in India. This analysis will focus on the number of Malaysian student in India from 1947 until 1990, their birth places in Malaysia, the year they reached India, the name of their institution in India, the main factor of their studies in India and introduction with some of the Malaysian scholars graduated from these institutions. These findings will benefit researchers in giving a general view of the importance of Islamic India institution and it significant in producing quality Malaysian scholars in Islamic studies.